2005
DOI: 10.1007/s00125-005-1896-y
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of left ventricular hypertrophy in type 2 diabetes mellitus

Abstract: Aims/hypothesis: Patients with type 2 diabetes mellitus are at greater cardiovascular risk than the general population. Although it is widely acknowledged that diabetes is a risk factor for coronary artery disease, the increased prevalence of potentially lethal left ventricular abnormalities in this population is less well appreciated. Methods: We carried out an echocardiographic study of 500 subjects with type 2 diabetes mellitus to assess the prevalence of left ventricular hypertrophy (LVH) and left ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 58 publications
(54 reference statements)
4
74
2
3
Order By: Relevance
“…This is particularly significant as LVH is also associated with various metabolic abnormalities, such as central obesity, dyslipidemia, insulin resistance, and type 2 DM, even in the absence of hypertension. 6 Hence, LVH and albuminuria are both markers for CVDs in patients with type 2 DM. Studies in diabetics with microalbuminuria (which usually precedes macroalbuminuria by an interval of 5-10 years) have shown that increased albumin leakage in the glomerulus is linked to enhanced capillary permeability for albumin in the systemic vasculature as well.…”
Section: Associations Of Lvmi and Uacr With Pertinent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly significant as LVH is also associated with various metabolic abnormalities, such as central obesity, dyslipidemia, insulin resistance, and type 2 DM, even in the absence of hypertension. 6 Hence, LVH and albuminuria are both markers for CVDs in patients with type 2 DM. Studies in diabetics with microalbuminuria (which usually precedes macroalbuminuria by an interval of 5-10 years) have shown that increased albumin leakage in the glomerulus is linked to enhanced capillary permeability for albumin in the systemic vasculature as well.…”
Section: Associations Of Lvmi and Uacr With Pertinent Variablesmentioning
confidence: 99%
“…Type 2 DM patients thus are at increased risk of CVS complications due to adverse CVS effects of DM in addition to the traditional risk factors of associated increases in Body mass index (BMI), arterial pressure and dyslipidemia. 6 Therefore, the early identification of such patients at greatest risk of increased CVS complications is of utmost importance so that potentially lifesaving treatment can be initiated at the earliest.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is acknowledged as a principal risk factor for cardiovascular morbidity and mortality and has a heavy impact on the global health expenditure due to both its short and long term complications. 2 DM is closely linked to coronary events 3 and left ventricular hypertrophy (LVH) in DM patients has been widely implicated 4,5 and therefore considered as a treatment target 5 , as associated cardiovascular risks become normal with full regression of LVH. 6 Insulin resistance and associated abnormal glucose metabolism have been implicated in many reports as a possible pathophysiological mechanism of LVH.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Liao et al in black adults in 1995, LVH was found to be a stronger risk factor, and accounted for more deaths than did multivessel coronary artery disease 4. Furthermore, LVH is remarkably common: using the new LVH criteria of the American Society of Echocardiography, the prevalence of LVH approaches 70% in patients with stable angina, with similar figures for those with diabetes 5 6…”
mentioning
confidence: 99%